Чисельне моделювання функції розподілу електронів за енергіями для рівняння Больцмана та інших параметрів плазми розряду - Василь, Чигінь; Павло, Горун (Видавництво Національного університету «Львівська політехніка», 2009)
Using processed numerical methods, were founded and compared the electron energy distribution functions for Bolzmann equation, that was represented in stationary case, electronic processes rates, power loss coefficients and other parameters of negative corona in the mixture of Ar-Kr-Xe and Cl2.
Keywords: чисельне моделювання; коронний розряд; рівняння Больцмана